Peran Wanita Bungo dalam Mempertahankan Kemerdekaan Tahun 1945-1949 - Sihaloho, Diana Angela; Sudeli, Seri (Prodi Ilmu Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, 2024)
After the Japanese occupation period ended in Indonesia, it was marked by Japan's surrender due to bomb attacks in Horoshima and Nagasaki. The bomb attacks came from the Allies as an attempt at revenge, Japan's defeat seemed to open the way for Indonesian independence. As a result of this defeat, Japan gave the promise of independence to the Indonesian people by the Prime Minister of Tokyo. However, colonialism in Indonesia continued, with the return of allies supported by NICA in various areas, especially the Muara Bungo area. Muara Bungo women participated in defending and maintaining Indonesian independence. The aim of this research is to determine the role of Muara Bungo women in defending independence. The research method used is the historical method, with stages; heuristics, criticism, interpretation, and historiography. The data collection techniques used were observation, interviews and literature study. The results of this research are that Muara Bungo women were directly involved both on the front lines and in public kitchens in maintaining independence from colonial attacks.